Musykilāt Tadrīs Mahārah al-Kalām fī Maʻhad Dār aṭ-Ṭālibīn al-Qādiri 2 Gumukmas Jember - Nor Holis Bin Nafsah; Ahmad Mizan Rosyadi Abdul Jalil Manan (Al-Fusha : Arabic Language Education Journal, 2021)
Learning Arabic that is applied to the Darut Tholibin Al-Qodiri 2 Gumukmas Islamic Boarding School in Jember has left problems, especially in the field of mahārah kalām. Mahārah kalām is a skill that requires students to be active in communicating verbally using Arabic. This article aimed to describe the problems of learning Arabic in the field of mahārah kalām to students of Darut Tholibin Al-Qodiri 2 Islamic Boarding School Gumukmas Jember. Researchers used qualitative methods to discuss the problems of learning Arabic in mahārah kalām. The data showed that there are two types of problems faced by students of the Darut Tholibin Al-Qodiri 2 Gumukmas Islamic Boarding School in Jember; linguistic problems and non-linguistic problems. Linguistic problems related to the system of morphology, syntax, and semantics. Meanwhile, non-linguistic problems were related to sociological, psychological, and pedagogical issues. This problem becomes an obstacle for students to achieve success in learning Arabic.